(untitled) (Herald of Journalism, 2019)
The formation of an intellectual nation is recognized as one of the strategic objectives of the development of Kazakhstan, where the main vectors are quality education and the support of the younger generation. According to reviews of foreign specialists in the field of education, as well as the results of contests, tests, etc. The Kazakh youth have a high level of intellectual potential. The only thing we need is to be able to use it correctly. It is not so easy to give a good education to a future specialist, and also to help him discover his talent and abilities, create conditions for the skillful use of the knowledge gained, and ensure the formation of competitive employees. From a strategic point of view, it is important to identify indicators that are most closely associated with economic (or otherwise desirable) growth. On the other hand, if the analysis is carried out on a national scale, it becomes obvious that even the national specific economic incentives of the Intellectual nation can be identified. This article focuses on the formation of the “intellectual nation” of the society of 21st century, when a creative person becomes the main source of development. The purpose of the work is to reveal the features of the formation of intellectual capital in Kazakhstan in the focus of humanitarian technologies. The research methodology of the scientific work contains methods of system analysis: methods of social experiment; behavioral methods of research of social phenomena, methods of social design, social engineering, sociometric studies; dialogue methods for humanitarian studies. The main results are studied theoretical issues and practical application of humanitarian technology; The analysis of rethinking, popularization and transformation of the development of intellectual capital. The value of the study in the comprehensive study of modernization in Kazakhstan; in fundamental and applied research in the field of humanitarian technologies. The scientific and practical significance of the work is determined in the development of scientific concepts, the implementation of state information policy, in the implementation of integrated programs; in the activities of national, international centers; in forecasting the prospects for the development of the ideological concept of “Ruhani zagyru”. The practical significance of the work results is that the research results are applicable in the field of mass communication, political science, sociology, cultural studies.